Impaired Neural Synchrony in the Theta Frequency Range in Adolescents at Familial Risk for Schizophrenia - Donkers, Franc C.; Schwikert, Shane R.; Evans, Anna M.; Cleary, Katherine M.; Perkins, Diana O.; Belger, Aysenil (Frontiers in Psychiatry, 2011)
Puberty is a critical period for the maturation of the fronto-limbic and fronto-striate brain circuits responsible for executive function and affective processing. Puberty also coincides with the emergence of the prodromal signs of schizophrenia, which may indicate an association between these two processes. Time-domain analysis and wavelet based time-frequency analysis was performed on electroencephalographic (EEG) data of 30 healthy comparison (HC) subjects and 24 individuals at familial risk for schizophrenia (FR). All participants were between the ages of 13 and 18 years and were carefully matched for age, gender, ethnicity, education, and Tanner Stage. Electrophysiological recordings were obtained from 32 EEG channels while participants performed a visual oddball task, where they identified rare visual targets among standard ‘scrambled’ images and rare aversive and neutral distracter pictures. The time-domain analysis showed that during target processing the FR group showed smaller event-related potentials (ERPs) in the P2 and P3 range as compared to the HC group. In addition, EEG activity in the theta (4-8 Hz) frequency range was significantly reduced during target processing in the FR group. Inefficient cortical information processing during puberty may be an early indicator of altered brain function in adolescents at familial risk for schizophrenia and may represent a vulnerability marker for illness onset. Longitudinal assessments will have to determine their predictive value for illness onset in populations at familial risk for psychotic illness.